Phase transitions between tropical, subtropical, and extratropical cyclones: A review from IWTC-10 - Wood, Kimberly; Yanase, Wataru; Beven, Jack; Camargo, Suzana J.; Courtney, Joseph B.; Fogarty, Chris; Fukuda, Junya; Kitabatake, Naoko; Kucas, Matthew; McTaggart-Cowan, Ron; Reboita, Michelle Simões; Riboldi, Jacopo (Elsevier, 2023)
This review, which was adapted from a Tenth International Workshop on Tropical Cyclones (IWTC-10) report, discusses research findings and operational practices relevant to cyclone types and phase transitions (extratropical, subtropical, and tropical). The cyclone phase space (CPS) method is widely used in both historical investigations and real-time evaluation of cyclone type and transition; however, CPS parameter values depend on input data resolution, and universal thresholds do not currently exist to delineate when a cyclone transitions from one type to another. Assessments of phase transitions in a changing climate highlight potential latitude shifts in extratropical transition and increased potential for tropical transition, but realistic projections of future trends likely require high-resolution simulations that can capture the cyclone warm core. Operational meteorological centers apply varied approaches to cyclone classification via CPS parameters and other criteria, some of which depend on the tropical basin, yet these approaches cannot fully address challenges in operational classification and subsequently in communicating risks associated with these phase transitions. We recommend a multivariate historical assessment of tropical and subtropical cyclones across all basins in which they occur, including the South Atlantic Ocean and the Mediterranean Sea, to identify the potential for a more universal cyclone classification approach that meets operational needs. ISSN:2589-3025 ISSN:2225-6032